Pengaruh Keamanan dan Online Customer Review terhadap Keputusan Pembelian pada Marketplace Lazada - Wildan Jamil; Sugeng Purwanto (Universitas Batanghari, 2022)
Online shopping is becoming a trend in today's modern era, one of which is the Lazada marketplace. Lazada is one of the leading marketplaces in Indonesia. However, in recent years Lazada has been displaced by its competitors. This study had a puurpose to determine the that security and online customer reviews affected the customers of Lazada Marketplace purchasing decisions. Sampling technique used is non-probability sampling using smartPLS as an analytical tool. Data obtained from questionnaires distributed via google form with a total sample of 96 respondents. The results of this study indicate that security and online customer reviews affects purchasing decisions on the Lazada marketplace.